Onomastic space of Rasul Gamzatov's works - Ruganiyat A. Musayeva (Кавказология)
The article examines the onomastic space of poetry by the outstanding poet of the 20th century Rasul Gamzatov. This study reveals the role of proper names in the poet’s work, reflects the importance of onyms in the realization of the creative idea of the works, in reflecting the individual author’s picture of the world. The article classifies proper names according to semantic and structural categories. The analysis of onyms is conducted and their place in the “core-periphery” system of the onomastic field is determined. In the onomastic space of the works of the author under study, it was possible to identify the following types of onyms that can be classified as paratextual: designation, title, epigraph, dedication. During the analysis of the onomastic space, it was established that proper names, both intertextual and paratextual, play an important and organic role in the stylistic system of the author’s texts, since, possessing a wealth of semantic connections, complex associations and connotations, contribute to the formation of the general imagery of Rasul Gamzatov’s works.